М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
тетрадках
тетрадках
19.10.2022 10:05 •  Алгебра

Решить мне решение а в квадрате-49=(а-7)

👇
Ответ:
grbennikovigor
grbennikovigor
19.10.2022

a квадрат - 49 = a- 7

a квадрат - а - 42 = 0

                 D = 1 + 4 * 1 * 42 = 169

                 корень D = 13

                a1 = -6

                a2 = 7

4,8(37 оценок)
Ответ:

a²-49=a-7

a²-7²=a-7

(a+7)(a-7)=a-7

(a+7)(a-7)-(a-7)=0

(a-7)(a+7-1)=0

(a-7)(a+6)=0

1)a-7=0, a=7

2)a+6=0, a=-6


(x × y=0 ⇔ x=0 ∨ y=0)

4,6(91 оценок)
Открыть все ответы
Ответ:
lizonkagrbnw
lizonkagrbnw
19.10.2022

1) x^2-4x+3=0

ax^2+bx+c=0

a=1

b=-4

c=3

D=b^2-4ac=(-4)^2-4*1*3=4

2) -x^2-x+6=0

ax^2+bx+c=0

a=-1

b=-1

c=6

D=b^2-4ac=(-1)^2-4*(-1)*6=25

3) 5x^2+3x-8=0

ax^2+bx+c=0

a=5

b=3

c=-8

D=b^2-4ac=3^2-4*5*(-8)=169

4) 9x^2-12x+4=0

ax^2+bx+c=0

a=9

b=-12

c=4

D=b^2-4ac=(-12)^2-4*9*4=0

5) 2x^2+x+2=0

ax^2+bx+c=0

a=2

b=1

c=2

D=b^2-4ac=1^2-4*2*2=-15

6) -3x^2+13x-12=0

ax^2+bx+c=0

a=-3

b=13

c=-12

D=b^2-4ac=13^2-4*(-3)*(-12)=169-144=25

7) 3x^2-6x+2=0

ax^2+bx+c=0

a=3

b=-6

c=2

D=b^2-4ac=(-6)^2-4*2*3=12

8) -25x^2+8x-1=0

ax^2+bx+c=0

a=-25

b=8

c=-1

D=b^2-4ac=8^2-4*(-25)*(-1)=-36

9) x^2-4x-5=0

ax^2+bx+c=0

a=1

b=-4

c=-5

D=b^2-4ac=(-4)^2-4*1*(-5)=36

10) -6x^2+5x-1=0

ax^2+bx+c=0

a=-6

b=5

c=-1

D=b^2-4ac=5^2-4*(-6)*(-1)=1

4,5(59 оценок)
Ответ:
flanchase
flanchase
19.10.2022

1)3x+2y=12              2)3x-y=4| *3

 x+2y=-4|*(-1)             2x+3y=21

 

3x+2y=12                9x-3y=12

 -x-2y=4                 2x+3y=21      

 

2x=16                     11x=33

  x=8                        x=3

 

3*8+2y=18              2*3+3y=21

  2y=-6                   3y=15

   y=-3                     y=5

3)x-y=3                   4)4x+3y=10|*(2)

 -x-4y=7                    x-2y=-3|*3

 -5y=10                     8x+6y=20

  y=-2                       3x-6y=-9

  x-(-2)=3                   11x=11

  x=1                          x=1

                                1-2y=-3

                               

                                -2y=-4

                                 y=2

 

Объяснение:

4,5(29 оценок)
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ